Laplacian flow for closed G2 structures: real analyticity - Lotay, J; Wei, Y (International Press of Boston, 2019)
Let φ(t),t∈[0,T0] be a solution to the Laplacian flow for closed G2 structures on a compact 7-manifold M. We show that for each fixed time t∈(0,T0],(M,φ(t),g(t)) is real analytic, where g(t) is the metric induced by φ(t). Consequently, any Laplacian soliton is real analytic and we obtain unique continuation results for the flow.